PENGEMBANGAN MEDIA PEMBELAJARAN PostDo (POSTER DAN EDMODO) PADA MATERI EKSKRESI MANUSIA - Prasmala, Erfitra Rezqi; Agustin, Khusnia; Irmawati, Farizha (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to find out how the development of PostDo as a learning medium on human excretory system material. This research was a development-research with a 4D development model consisting of 4 main stages, namely: Define, Design, Develop, Disseminate which will later produce PostDo learning media with a combination of Poster and Edmodo. Based on the validation results of validators of PostDo media obtained a score of 4.4 with